2015
DOI: 10.1371/journal.pone.0121200
|View full text |Cite
|
Sign up to set email alerts
|

Second-Hand Cigarette Smoke Impairs Bacterial Phagocytosis in Macrophages by Modulating CFTR Dependent Lipid-Rafts

Abstract: IntroductionFirst/Second-hand cigarette-smoke (FHS/SHS) exposure weakens immune defenses inducing chronic obstructive pulmonary disease (COPD) but the underlying mechanisms are not fully understood. Hence, we evaluated if SHS induced changes in membrane/lipid-raft (m-/r)-CFTR (cystic fibrosis transmembrane conductance regulator) expression/activity is a potential mechanism for impaired bacterial phagocytosis in COPD.MethodsRAW264.7 murine macrophages were exposed to freshly prepared CS-extract (CSE) containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 72 publications
(151 reference statements)
2
50
0
Order By: Relevance
“…The disease kills more than 120,000 Americans each year and the number of people with COPD is increasing [56]. Each year, about 300,000 people die in Europe due to COPD [77], and the morbidity, disability, economic and social impact of COPD is substantial and increasing. The…”
Section: Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease kills more than 120,000 Americans each year and the number of people with COPD is increasing [56]. Each year, about 300,000 people die in Europe due to COPD [77], and the morbidity, disability, economic and social impact of COPD is substantial and increasing. The…”
Section: Copdmentioning
confidence: 99%
“…The loss of CFTR function induced by cigarette smoke exposure is also associated with loss of lipid raft CFTR, increased membrane ceramide accumulation and increased apoptosis [76]. It has also been shown that altered CFTR lipid rafts in macrophage exposed to cigarette smoke impair macrophage bacterial phagocytosis and killing, which might contribute to recurrent bacterial infections in the disease [77]. Interestingly, it has been reported that COPD patients with a history of disease exacerbations during the past year exhibited less CFTR function than those without a history of exacerbations, further emphasizing the clinical consequences associated with acquired CFTR dysfunction in COPD [67].…”
mentioning
confidence: 99%
“…al., have shown that SHS significantly reduces phagocytic clearance of pathogenic bacteria by affecting CFTR function in macrophages, extending potential manifestations beyond the airway. 89 The detrimental effects of SHS warrant further investigation into the mechanistic basis and physiologic significance underlying airway epithelial dysfunction in passive smokers, including its potential to contribute to COPD and respiratory infections, such as acute bronchitis or otitis media in the young. 90,91 …”
Section: Second Hand Smokingmentioning
confidence: 99%
“…This implies CFTR dysfunction by SHS may also account for increased infectious burden among passive smokers [47]. Consistent with this notion, Ni et al have reported that SHS significantly reduces phagocytic clearance of bacteria by depleting membrane expression of CFTR in macrophages extending the pathologic significance of CFTR dysfunction beyond the airway epithelium [48].…”
Section: Discussionmentioning
confidence: 81%